Ecotourism: A Key Strategy in Realizing Indonesia's Golden Age By 2045 - Sabalius Uhai; Novita Indriani; Gia Puspita Mokodompit; Galuh Yeni Maisaroh; Rini Koen Iswandari (Yayasan Inovasi Kemajuan Intelektual, 2025)
Approaching its centenary of independence in 2045, Indonesia faces a significant challenge in transforming its economic structure from a dependency on extractive resources to a sustainable economy. Ecotourism has emerged as a key strategy that not only drives economic growth but also supports biodiversity conservation and social empowerment. This study aims to analyze the strategic role of ecotourism in supporting the pillars of the Golden Indonesia 2045 vision. Using a qualitative descriptive method and a literature review, this study evaluates Indonesia's natural resource potential and its integration with national development policies. The results show that ecotourism can be an engine of inclusive green economic growth, creating jobs in remote areas and strengthening Indonesia's image internationally as a leader in climate change mitigation. The study's conclusion emphasizes that synergy among government regulations, digital infrastructure readiness, and local community involvement is an essential for ecotourism to contribute optimally to realizing Indonesia as a developed, sustainable nation by 2045.